(untitled) (Research, Society and Development, 2021)
The present work approaches the school as a control institution, in the last decades, from the analysis of educational memories produced during the “Supplementary Teaching Project: History and Historiography of Education in Rio Grande do Norte”, carried out by the Federal University of Rio Grande do Norte, in the supplementary semester of 200.5. In order to analyze the collected materials, paying attention to the control devices found in the participants’ memories. Methodologically, the reports present in the memorials were selected and cataloged, starting from topics and subtopics of analysis, using thematic analysis as a form of analysis. Theoretically, Michel Foucault corroborated with the understanding of control devices and disciplinary society, in particular, and Le Goff with the conception of memory. The results were the cataloging of about seventy-five educational memorials, within the themes of analysis, thus proceeding to the conclusion that the research pointed to the importance of memories as a formative element and how the control devices within the analyzed educational memories.